2014
DOI: 10.1097/mao.0000000000000580
|View full text |Cite
|
Sign up to set email alerts
|

Revision Stapedectomy With Bone Cement

Abstract: Use of hydroxyapatite cement for treatment of incus necrosis in revision stapedectomy provides excellent hearing outcomes and is a reasonable alternative to total ossicular reconstruction prosthesis or malleovestibular prosthesis techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Since dislocations commonly occur towards the inferior, a drop of bone cement applied to the distal end of the LPI would prevent most of the dislocations. 6,9 Applying to both sides of the loop or bridging over the loop could even give better stabilization. But it should not be forgotten that increasing the weight of the ossicular chain could deteriorate high-frequency hearing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since dislocations commonly occur towards the inferior, a drop of bone cement applied to the distal end of the LPI would prevent most of the dislocations. 6,9 Applying to both sides of the loop or bridging over the loop could even give better stabilization. But it should not be forgotten that increasing the weight of the ossicular chain could deteriorate high-frequency hearing.…”
Section: Discussionmentioning
confidence: 99%
“…The causes of revision stapedotomy include loose prosthesis, LPI necrosis-mainly due to overtight wire loop prostheses, or dislocations. 6 Bone cement application may prevent loose prostheses and dislocations. If bone cement stabilization is planned, the surgeon may depend on the bone cement for ensuring a tight fixation and avoid overtightening.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While there were mixed results in early experiences using bone cement in stapes surgery, more recent studies have demonstrated excellent audiologic outcomes in revision cases. 13,[19][20][21][22] In some of the more robust series of 27 to 37 patients, post-operative ABG have ranged from 8.1 dB to 8.8 dB, with short-term closure to within 10 dB seen in 77% and 81% of cases. 13,20 Our study demonstrated similar ABG closures to an average of 9 dB in a larger cohort of 46 patients, and 78% closed to within 10 dB.…”
Section: Discussionmentioning
confidence: 99%